Guernsey : Financial Sector Assessment Program Update-Technical Note on Stress Testing; Banking and Insurance. (IMF Staff Country Reports; Country Report ;, 2011)
Stress testing (ST) was undertaken as part of the Guernsey Financial sector assessment Program (FSAP) Update in order to assess the resilience of the Guernsey financial system to a variety of potential strains. The approach taken was a simulation of the effect of a potential double-dip recession on solvency of Guernsey banks and insurance companies. The STs assess the sensitivity of banks and insurance companies to single-factor shocks to risk types affecting solvency and liquidity position of institutions. The mission recommends that future STs should be risk-based and that macroprudential analysis should be run on a regular basis.